2019
DOI: 10.3324/haematol.2018.198622
|View full text |Cite
|
Sign up to set email alerts
|

Factor H interferes with the adhesion of sickle red cells to vascular endothelium: a novel disease-modulating molecule

Abstract: Sickle cell disease is an autosomal recessive genetic red cell disorder with a worldwide distribution. Growing evidence suggests a possible involvement of complement activation in the severity of clinical complications of sickle cell disease. In this study we found activation of the alternative complement pathway with microvascular deposition of C5b-9 on skin biopsies from patients with sickle cell disease. There was also deposition of C3b on sickle red cell membranes, which is promoted locally by the exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…Hemolysis‐derived products or anti‐endothelial antibodies present in the serum could explain this activation. This complement over activation is concordant with the complement‐mediated cytotoxicity from SCD patients' sera (modified Ham's test), the enhanced C3 deposits on ECs exposed to SCD RBC microvesicles, and the endothelial C3 deposits in tissues of SCD mice and biopsies of patients . This over activation is indeed at least in part heme‐dependent since it was inhibited by the heme scavenger hemopexin.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Hemolysis‐derived products or anti‐endothelial antibodies present in the serum could explain this activation. This complement over activation is concordant with the complement‐mediated cytotoxicity from SCD patients' sera (modified Ham's test), the enhanced C3 deposits on ECs exposed to SCD RBC microvesicles, and the endothelial C3 deposits in tissues of SCD mice and biopsies of patients . This over activation is indeed at least in part heme‐dependent since it was inhibited by the heme scavenger hemopexin.…”
Section: Discussionsupporting
confidence: 65%
“…Taken together, recent mouse models and data from patients suggest that complement plays a key role in the SCD disease process and is a potential therapeutic target . The HU treatment resulted in prevention of complement activation on blood cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Increased soluble C5b-9 levels have been reported in SCD patients (53,54). Vercellotti et al (55) demonstrated increased C3 activation fragments and C5b-9 in the kidneys, lungs and liver of sickle cell mice, compared to control mice, and Lombardi et al (56) found increased microvascular deposition of C5b-9 on skin biopsies in SCD patients. Increased alternative pathway Bb fragments have also been reported in the plasma of both sickle cell mice and sickle cell patients (55,57).…”
Section: Hemolysis and The Alternative Complement Pathwaymentioning
confidence: 99%
“…The infusion of recombinant C5a has been shown to cause blood stasis and inflammation in the liver of sickle cell mice (through NF-κB activation and increased expression of TLR4 and several adhesion molecules), but this response was reversed by an anti-C5a receptor IgG (55). The increased externalization of phosphatidylethanolamine and phosphatidylserine at the membrane of sickle RBCs is also suspected to induce complement activation with increased C3 and C3b binding (56,57). A very recent work investigated the role of heme on complement activation in the context of SCD (58).…”
Section: Hemolysis and The Alternative Complement Pathwaymentioning
confidence: 99%